2015
DOI: 10.1371/journal.pone.0129119
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1, -3 and -9 Expression and Clinical Significance in Squamous Cervical Cancer

Abstract: Galectins are proteins that bind β-galactoside sugars and provide a new type of potential biomarkers and therapeutic targets in cancer. Galectin-1, -3 and -9 have become the focus of different research groups, but their expression and function in cervical cancer is still unclear. The aim of this study was to determine the phenotype of galectin-1, -3 and -9 expressing cells and the association with clinico-pathological parameters in cervical cancer. Galectin expression was scored in tumor cells, tumor epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 47 publications
8
54
2
Order By: Relevance
“…It has been associated with tumor proliferation, angiogenesis, and metastasis . Galectin‐1‐secreting tumors gain immune privilege by inducing apoptosis in T‐helper cells, and its expression level correlates with the aggressiveness of certain tumors . Many of these processes are mediated by the sophisticated interplay between the lectin and the β‐galactosides of complex glycan structures presented on the cell surface.…”
Section: Figurementioning
confidence: 80%
“…It has been associated with tumor proliferation, angiogenesis, and metastasis . Galectin‐1‐secreting tumors gain immune privilege by inducing apoptosis in T‐helper cells, and its expression level correlates with the aggressiveness of certain tumors . Many of these processes are mediated by the sophisticated interplay between the lectin and the β‐galactosides of complex glycan structures presented on the cell surface.…”
Section: Figurementioning
confidence: 80%
“…Apart from possible applications in nuclear imaging, we also evaluated the use of the antibodies in immunohistochemical analyses. Immunohistological stainings on tissues can reveal the (sub)cellular distribution of galectin‐1, which has been shown to be of added value for galectins . For example, elevated galectin‐1 expression in malignant tissues is frequently confined to the stromal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, deregulated expression or function of galectin‐1 is frequently associated with disease, most notably with inflammatory disorders and cancer . Regarding the latter, we and others have shown that increased galectin‐1 expression is associated with poor survival in many cancer types . This has been attributed to the capacity of galectin‐1 to suppress the anti‐tumor immune response, to induce tumor angiogenesis, and to promote tumor metastasis .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…[2] Galectin-1-secreting tumors gain immune privilegeb y inducing apoptosis in T-helperc ells, [3] andi ts expression level correlates with the aggressiveness of certain tumors. [4] Many of these processes are mediated by the sophisticated interplay between the lectin and the b-galactosides of complex glycan structures presented on the cell surface. Owing to the overexpression of galectin-1 in numerous types of cancerc ell lines, the protein has been suggested as ap otential target for therapeutic intervention [5] and ad iagnostic marker.…”
Section: Dedicatedtoprofessor Lutz Friedjan Tietze On the Occasion Ofmentioning
confidence: 99%